Iron isotope compositions of subduction-derived rocks: Insights from eclogites and metasediments of the Münchberg Massif (Germany) - Pohlner, Johannes E.; El Korh, Afifé; Chiaradia, Massimo; Klemd, Reiner; Grobéty, Bernard; Pettke, Thomas (Chemical Geology, 2022)
The Fe isotope systematics of subducted lithologies are crucial for the understanding of redox-dependent mass transfer in subducting slabs, with consequences for the compositions of arc magmas and of the deep mantle. We investigated eclogites, metagabbros, and paragneisses from the Variscan Münchberg Massif to unravel whether their Fe isotope compositions are dominated by the igneous/sedimentary protolith signature, by low-temperature seawater alteration, or by later fluid-rock interactions during the subduction-exhumation cycle. Although the eclogites are thought to be derived from a continental rather than oceanic setting (possibly a rift-drift transition stage), they have mid-ocean ridge basalt (MORB)-like major and trace element compositions. They are often moderately oxidized compared to MORB (Fe3+/ΣFe = 0.06 to 0.30). Their δ56Fe values (+0.00 to +0.17‰; mean + 0.08 ± 0.01‰) mostly resemble those of MORB (+0.07 to +0.17‰). The metagabbros, which are derived from a more enriched mantle source than the eclogites, yielded heavier δ56Fe values (+0.09 to +0.22‰) similar to ocean island basalts, whereas those of the paragneisses (+0.03 to +0.10‰) are typical for pelitic sediments. It appears that the Fe isotope compositions of the igneous protoliths are largely preserved and little if any Fe was mobilized during the diverse fluid-rock interaction stages. The parental magma of the eclogites was probably somewhat isotopically lighter than similarly differentiated MORB magmas, perhaps due to the presence of metasomatized, isotopically light peridotites in the subcontinental lithospheric mantle (SCLM) source. Although it is possible that δ56Fe values were slightly modified during seawater alteration and/or metamorphic fluid-rock interactions in some of the eclogites, the impact of fluid-rock interactions on the major element compositions of the eclogites appears to be small. Furthermore, the scarcity of metamorphic veins in the Münchberg Massif argues against significant Fe mobilization in the slab. We suggest that continental eclogites tend to retain their magmatic δ56Fe values throughout the subduction-exhumation cycle, whereas δ56Fe values of oceanic eclogites may often be dominated by seafloor alteration with potential local modifications in the slab close to fluid channels. The remarkable robustness of the Fe isotope compositions of continental eclogites suggests that they may be used to reconstruct protolith mantle source properties despite the complex post-magmatic history.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Eclogites; Fe isotopes; Fluid-rock interactions; Subduction